2023
DOI: 10.3390/ph16081100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of the TRPC4/TRPC5 Blocker, ML204, in Sucrose-Induced Metabolic Imbalance

Abstract: Sugar-induced metabolic imbalances are a major health problem since an excessive consumption of saccharides has been linked to greater obesity rates at a global level. Sucrose, a disaccharide composed of 50% glucose and 50% fructose, is commonly used in the food industry and found in a range of fast, restaurant, and processed foods. Herein, we investigated the effects of a TRPC4/TRPC5 blocker, ML204, in the metabolic imbalances triggered by early exposure to sucrose-enriched diet in mice. TRPC4 and TRPC5 belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It has been shown that mice subjected to a high-sucrose diet display signs of inflammation in their adipose tissue and liver, marked by elevated levels of pro-inflammatory cytokine TNFα [37], a cytokine associated with adipocyte enlargement, fat accumulation, insulin resistance, and elevated blood sugar levels. Previously, we discovered that TNFα significantly decreased CcO activity in mouse liver tissue through downstream phosphorylation of Y304 residue of CcO catalytic subunit I, resulting in a sharp decline in mitochondrial membrane potential and a reduction in cellular ATP levels [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mice subjected to a high-sucrose diet display signs of inflammation in their adipose tissue and liver, marked by elevated levels of pro-inflammatory cytokine TNFα [37], a cytokine associated with adipocyte enlargement, fat accumulation, insulin resistance, and elevated blood sugar levels. Previously, we discovered that TNFα significantly decreased CcO activity in mouse liver tissue through downstream phosphorylation of Y304 residue of CcO catalytic subunit I, resulting in a sharp decline in mitochondrial membrane potential and a reduction in cellular ATP levels [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the TRPC3 channel enhances sensitivity in gustatory perception of dietary lipids, potentially influencing preferences for lipid intake and thereby affecting the occurrence of obesity ( Murtaza et al, 2021 ). On the other hand, TRPC4/TRPC5 has been shown to protect against hyperglycemia and dyslipidemia caused by a high-sucrose diet ( Araujo et al, 2023 ). However, interestingly, deletion of TRPC5 in the central amygdala has been shown to counteract obesity induced by a high-fat diet through an increase in sympathetic innervation ( Ma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%